Thyroid Dysfunction in Patients with Metabolic Syndrome: A Cross-Sectional, Epidemiological, Pan-India Study - Vaishali Deshmukh; Faraz Farishta; Milind Bhole (International Journal of Endocrinology)
Background. This study was conducted to assess the prevalence and clinical and epidemiological factors of thyroid dysfunction (TD) in Indian patients diagnosed with metabolic syndrome (MetS). Methods. In this cross-sectional study, 432 adults with an established diagnosis of MetS were enrolled across ten centers in India. Anthropometric measurements and vital signs were noted. Blood samples were tested for hemogram, coagulogram, lipid profile, and thyroid function. Fasting plasma glucose (FPG) and fasting plasma insulin were used for the calculation of homeostasis model assessment-estimated insulin resistance (HOMA-IR). Overt hypothyroidism was defined as thyroid-stimulating hormone TSH>4.50 μIU/mL with free thyroxine FT4<0.8 ng/dL and free triiodothyronine FT3<1.4 pg/mL; subclinical hypothyroidism as TSH>4.50 μIU/mL with FT4=0.8-1.8 ng/dL and FT3=1.4-4.4 pg/mL; overt hyperthyroidism as TSH<0.45 μIU/mL with FT4>1.8 ng/dL and FT3>4.4 pg/mL; and subclinical hyperthyroidism as TSH<0.45 μIU/mL with FT4=0.8-1.8 ng/dL and FT3=1.4-4.4 pg/mL. Results. About 121 out of 432 patients (28%) were diagnosed with TD (mean age±SD: 47.9±10.96 years), with women predominance (75% versus 25%). Most patients were in the >45 years of age group (men: 63%; women: 59%). TD was associated with high waist circumference (99.17%), reduced high-density lipoprotein-C (87.60%), raised HOMA-IR (86.78%), systolic blood pressure (77.69%), diastolic blood pressure (59.50%), fasting glucose (58.68%), and triglycerides (33.06%). Overt hypothyroidism was reported in 17.59% (N=76) of patients. Subclinical hypothyroidism, overt hypothyroidism, and subclinical hyperthyroidism were reported in 8.10%, 1.60%, and 0.70% patients with newly occurred TD, respectively. No case of overt hyperthyroidism was present in these patients. Conclusion. Hypothyroidism was the most common TD in Indian patients with MetS. A large proportion of TD cases diagnosed during the study highlight the need for vigilant thyroid screening in patients with MetS in a real-life setting.